2001
DOI: 10.1097/00001756-200101220-00039
|View full text |Cite
|
Sign up to set email alerts
|

Action monitoring, error detection, and the basal ganglia: an ERP study

Abstract: The error negativity (Ne or ERN) is an event-related brain potential component, which is assumed to reflect error detection. Recently it has been hypothesized that the basal ganglia are assumed to play a crucial role in error detection. In the present study we ask whether the Ne is altered in patients with Parkinson's disease (PD), who have an impaired function of the basal ganglia. We recorded the Ne in patients and in matched controls, while they performed different tasks that require a relatively high cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
111
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 20 publications
23
111
1
1
Order By: Relevance
“…These results parallel previous findings that the amplitude of the response ERN increases with increasing accuracy [7], because the system expects correct responses under conditions in which errors are few [4]. When taken together with the results of previous studies NEUROREPORT [4,22,23] (but see also [24]), these findings support the hypothesis that the ERN reflects a reward prediction error associated with the mesencephalic dopamine system. However, it has also been proposed that the feedback ERN reflects the affective significance or emotional valence of the eliciting stimulus [9,14].…”
Section: Discussionsupporting
confidence: 89%
“…These results parallel previous findings that the amplitude of the response ERN increases with increasing accuracy [7], because the system expects correct responses under conditions in which errors are few [4]. When taken together with the results of previous studies NEUROREPORT [4,22,23] (but see also [24]), these findings support the hypothesis that the ERN reflects a reward prediction error associated with the mesencephalic dopamine system. However, it has also been proposed that the feedback ERN reflects the affective significance or emotional valence of the eliciting stimulus [9,14].…”
Section: Discussionsupporting
confidence: 89%
“…(and also in Parkinson's patients; ref. 37). Thus, the present data provide further confirmation of a performance-monitoring circuit that includes PFC, ACC, and the basal ganglia.…”
Section: Discussionsupporting
confidence: 73%
“…The second interpretation relies on an alternate conception of ERN and CRN as related, but not identical, components (36,37). In this view, the CRN is thought to signal the outcome of a general, response-related monitoring process, and the ERN reflects this generic monitoring process plus error-specific activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that genotypic characteristics of subjects concerning D 2 receptor regulation (DRD2-TAQ-IA polymorphism) are correlated with learning strategies and with stronger activations of ACC and dorsolateral prefrontal cortex for performance feedbacks (Klein et al, 2007). Furthermore, several studies showed attenuated ERN in Parkinsonian patients, including at early stages of the disease (Falkenstein et al, 2001;Ito, 2004;Stemmer et al, 2007;Willemssen et al, 2008). However, the link between dopamine and FRP remains unresolved and its sensitivity to other neuromodulators needs to be further investigated (Jocham and Ullsperger, 2009).…”
Section: Perspectives For Chronic Observations Of Performance Monitoringmentioning
confidence: 99%